Preparation of natural chitosan from pens of squid Loligo spp. - Ahmad, Hawa Mas Azmar; Ab. Hadi, Hazrina; Md. Jaffri, Juliana (2015)
Natural chitosan derived from chitin can be obtained from crustacean shells as well as squid pen which usually considered as waste materials. Natural chitosan is biodegradable, biocompatible, non-toxic, anti-microbial, and possesses adsorption properties. Squid chitosan which is derived from β-chitin can be used as thickening agent in cosmetics formulation with advantage of scar removal property. The squid pens collected were washed and air dried before grounded into powder. 20 g of squid pen powder was treated in 300 mL of 1N hydrochloric acid for 2 hours in stirring condition for demineralisation. The mixture was filtered and washed with phosphate buffer pH 7 and dried in oven (60°C) overnight. Later, the demineralized powder was treated with 1M sodium hydroxide (NaOH) for 2 hours, filtered and washed with phosphate buffer pH 8 and dried in the dried in oven (60°C) overnight for deproteination. The deproteinated sample was further undergo deacetylation of chitin with 50% NaOH under reflux at 95°C for 3 hours using soxhlet apparatus. The deacetylated chitin was later washed with water, filtered, and dried in oven overnight. The dried chitin was purified into chitosan by dissolving in 1% acetic acid for 2 hours in stirring condition and filtered. The filtrate solution was later kept in -80°C freezer and dried in freeze dryer for 2 days. White powder or chitosan formed was weighed and its percentage yield was calculated. The chitosan was characterized using attenuated Fourier-Transform infrared spectroscopy (ATR-FTIR). Percentage yield obtained from the preparation of natural chitosan from squid pens was 3.5% (0.7 g). ATR-FTIR analysis showed that the natural chitosan has similar spectrum to the commercialized chitosan. The method used was convenient in terms of time-consumed and its productivity. A significant percentage yield of natural chitosan obtained from squid pen may turn waste materials into important and beneficial components.